Pencegahan Penyakit Paru Vaskular Obstruktif: Sebuah Laporan Kasus Pendekatan Tata Laksana pada CAVSD dengan PDA Besar - Hazami, Zakky; Putra, Bayushi Eka; Hendrarto, Toto Wisnu (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Background: Complete atrioventricular septal defect (CAVSD) and large patent ductus arteriosus (PDA) are considered as one of special conditionwhich need attention regarding its diagnosis and management. When CAVSD and large PDA is concomitant, the management is different from the simple case of CAVSD. Objective: Early recognition and optimal management of CAVSD and large PDA in area with limited medical facilities. Methods: This study will be presented as a case report. Case Illustration: A twenty-days-old female neonate was born with CAVSD and large PDA. The baby was in the 37 weeks gestational age when she was born spontaneously with APGAR score 8/9 and birth weight of 2890 g. Conservative approach was preferred as the patient was treated with captopril 0.8 mg three times a day, spironolactone 2mg twice a day and hydrochlorothiazide 1 mg twice a day to prevent heart failure. Conclusion: Pre-ductal and post-ductal oximetry test measurement is a reliable approach to screen patient with congenital heart disease which might be applied in medical center with limited medical facilities. Moreover, regarding the management, it might be beneficial to conduct early pulmonary artery banding.